Strategi Pengembangan Usaha Roti Ganto dalam Peningkatan Daya Saing di Kurao Pagang Kota Padang: Pendekatan Business Model Canvas - Nursa’diyah Nursa’diyah; Hesi Eka Putri (ARZUSIN, 2026)
Business development strategies and efforts to improve the competitiveness of micro, small, and medium enterprises (MSMEs) have received attention in various studies, but studies that specifically discuss the development of traditional bakery businesses through the Business Model Canvas approach remain relatively limited. This study aims to analyze the business development strategy of Usaha Roti Ganto in improving competitiveness in Kurao Pagang, Padang City. This study used a qualitative approach with a case study design. Informants were selected through purposive sampling, consisting of the business owner as the key informant, employees, customers, and other related parties with knowledge of business activities. Data were collected through interviews, observation, and documentation, and were then analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The results show that all elements of the Business Model Canvas have been applied in the operations of Usaha Roti Ganto, including customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. Business competitiveness is supported by affordable prices, taste quality that aligns with local community preferences, a strategic location, and customer loyalty. However, business development still faces constraints in the form of suboptimal customer segmentation, limited product innovation, low utilization of digital marketing, dependence on a single revenue source, and limited partnership networks. The conclusion of this study affirms that the Business Model Canvas is relevant for use as an analytical framework for the development of traditional bakery MSMEs. The implications of this study provide theoretical contributions to strengthening the literature on MSME business model development, as well as practical implications for business actors in designing more structured and sustainable competitiveness improvement strategies.